2019
DOI: 10.1111/sltb.12609
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Precision Treatment Rule for Remission of Suicide Ideation

Abstract: Objective There is growing interest in the development of composite precision treatment rules (PTRs) to guide the selection of the treatments most likely to be helpful for individual patients. We present here the results of an effort to develop a preliminary PTR for Collaborative Assessment and Management of Suicidality (CAMS) relative to enhanced‐care as usual based on secondary analysis of the Operation Worth Living (OWL) randomized controlled trial. The outcome of interest is eliminating suicide ideation (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This is important in the same way as it is important to evaluate a therapy against an active control rather than a waiting list. For instance, Kessler, Chalker, Luedtke, Sadikova, and Jobes (2020) used a rather advanced machine-learning ensemble to allocate optimal treatment for suicidal ideation among 148 U.S. soldiers. They found that this could increase 3-month remission of suicidal ideation with 13.6 % (albeit with a wide confidence interval between 0.9 -26.3%).…”
Section: Main Findingsmentioning
confidence: 99%
“…This is important in the same way as it is important to evaluate a therapy against an active control rather than a waiting list. For instance, Kessler, Chalker, Luedtke, Sadikova, and Jobes (2020) used a rather advanced machine-learning ensemble to allocate optimal treatment for suicidal ideation among 148 U.S. soldiers. They found that this could increase 3-month remission of suicidal ideation with 13.6 % (albeit with a wide confidence interval between 0.9 -26.3%).…”
Section: Main Findingsmentioning
confidence: 99%
“…Still absent from all such studies are data on the most effective intervention for a particular person at a particular time point-a longstanding question in mental health research and practice (17). Efforts to address questions such as this are currently underway (18,19) and hopefully will provide guidance that can be used to update the current consensus at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Such sample sizes are, for example, necessary to have sufficient statistical power to better understand the effects of CAMS on low base-rate outcomes like suicide attempts and to detect significant moderators of intervention effectiveness. Relatedly, recent research identifying significant moderators of CAMS effectiveness (e.g., marital status and baseline distress; Huh et al, 2018) that may be used to predict treatment response to CAMS (e.g., Kessler et al, 2020) underscores the need to further identify when, with whom, and under what conditions CAMS is most effective. Studies may also explore whether utilizing methods that leverage such moderators (e.g., Kessler et al, 2020) to determine optimal approaches for individual patients (e.g., CAMS versus an alternative intervention like DBT) improve treatment outcomes for those who are matched to their optimal approach.…”
Section: Future Directionsmentioning
confidence: 99%
“…Relatedly, recent research identifying significant moderators of CAMS effectiveness (e.g., marital status and baseline distress; Huh et al, 2018) that may be used to predict treatment response to CAMS (e.g., Kessler et al, 2020) underscores the need to further identify when, with whom, and under what conditions CAMS is most effective. Studies may also explore whether utilizing methods that leverage such moderators (e.g., Kessler et al, 2020) to determine optimal approaches for individual patients (e.g., CAMS versus an alternative intervention like DBT) improve treatment outcomes for those who are matched to their optimal approach. Researchers should also seek to incorporate repeated assessments of potential mechanisms of change (e.g., therapeutic alliance, increasing hope) in future studies, given that it is unclear the degree to which CAMS components individually contribute to enhanced treatment outcomes, which is also a concern with research on other suicide interventions (Fox et al, 2020); dismantling studies may also help clarify which components of CAMS are most effective in producing change.…”
Section: Future Directionsmentioning
confidence: 99%